Arsenic and cadmium bioavailability to rice (Oryza sativa L.) plant in paddy soil: Influence of sulfate application. (November 2022) - Yan, Shiwei; Yang, Jianhao; Si, Youbin; Tang, Xianjin; Ma, Youhua; Ye, Wenling
Abstract: Arsenic (As) and cadmium (Cd) accumulate easily in rice grains that pose a non-negligible threat to human health worldwide. Sulfur fertilizer has been shown to affect the mobilization of As and Cd in paddy soil, but the effect of co-contamination by As and Cd has not been explored. This study selected three soils co-contaminated with As and Cd from Shangyu (SY), Tongling (TL) and Ma'anshan (MA). Incubation experiments and pot experiments were carried out to explore the effect of sulfate supply (100 mg kg −1 ) on the bioavailability of As and Cd in soil and the rice growth. The results showed that the exogenous sulfate decreased As concentrations in porewater of SY and TL by 51.1% and 29.2% through forming arsenic-sulfide minerals. The exchangeable Cd in soil also declined by 25.6% and 18.6% and transformed into Fe and Mn oxides-bound Cd. The relative abundance of Desulfotomaculum, Desulfurispora and dsr gene increased remarkably indicated that sulfate addition stimulated the activity of sulfate-reducing bacteria. In MA soil, sulfate addition immobilized Cd but had little effect on As solubility, which was speculated to be related to the high sulfate background of the soil. Further pot experiments showed that sulfate application significantly increased rice tillers, biomass, chlorophyll content in shoots, and decreased electrolyte leakage in root. Finally, sulfate significantly reduced As and Cd in SY rice shoots by 60.2% and 40.8%, respectively, while As decreased by 39.6% in TL rice shoots and Cd decreased by 23.0% in MA rice shoots. These results indicate that the application of sulfate can reduce the bioavailability of As and Cd in the soil-rice system and promote rice growth, and it is possible to reduce the accumulation of As and Cd in rice plants simultaneously. Graphical abstract: Image 1 Highlights: Exchangeable Cd transformed into Fe and Mn oxides-bound Cd with sulfate addition. Sulfate application reduced As and Cd bioavailability simultaneously in paddy soil. Sulfate promoted the abundance of Desulfotomaculum and Desulfurispora. Sulfate improved rice growth and reduced As and Cd accumulation in rice seedlings.